2009
DOI: 10.1007/s12020-008-9143-1
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-rich diet-induced abdominal adipose tissue endocrine dysfunction in normal male rats

Abstract: We have currently studied the changes induced by administration of a fructose-rich diet (FRD) to normal rats in the mass and the endocrine function of abdominal (omental) adipose tissue (AAT). Rats were fed ad libitum a standard commercial chow and tap water, either alone (control diet, CD) or containing fructose (10%, w/vol) (FRD). Three weeks after treatment, circulating metabolic markers and leptin release from adipocytes of AAT were measured. Plasma free fatty acids (FFAs), leptin, adiponectin, and plasmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
82
0
17

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(117 citation statements)
references
References 31 publications
(44 reference statements)
18
82
0
17
Order By: Relevance
“…As previously reported, our FRD-fed rats presented insulin resistance, as demonstrated by hyperinsulinemia with normoglycemia and the HOMA-IR index, significantly increased serum triglyceride levels, impaired glucose tolerance and oxidative stress markers (Alzamendi et al, 2009;Francini et al, 2009Francini et al, , 2010Rebolledo et al, 2008).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As previously reported, our FRD-fed rats presented insulin resistance, as demonstrated by hyperinsulinemia with normoglycemia and the HOMA-IR index, significantly increased serum triglyceride levels, impaired glucose tolerance and oxidative stress markers (Alzamendi et al, 2009;Francini et al, 2009Francini et al, , 2010Rebolledo et al, 2008).…”
Section: Discussionsupporting
confidence: 85%
“…Although the underlying mechanism responsible for the detrimental effects of fructose-rich diets (FRD) is not quite clear, it is known that such diets promote an increase of glycoxidative stress (Busserolles et al, 2002;Girard et al, 2006;Lange et al, 1980;Thirunavukkarasu et al, 2004). In fact, we have previously demonstrated that short-term administration of a FRD to normal rats induces significant changes in many metabolic, endocrine and glycoxidative stress markers (Alzamendi et al, 2009;Francini et al, 2009Francini et al, , 2010Rebolledo et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have indicated that the PI3K/AKT pathway is associated with ROS production [26,38]. The PI3K/AKT pathway is included in protecting against not only ROS production but also apoptotic insults [39]. It has been suggested that quercetin showed anti-disease and anti-cancer activity via inhibiting ROS directly [40].…”
Section: Discussionmentioning
confidence: 99%
“…In these animals, we also recorded a marked increase in visceral adipose tissue (VAT) mass and impairment of its metabolic and endocrine functions [1][2][3].…”
Section: Introductionmentioning
confidence: 96%